Umbelliprenin via increase in the MECP2 and attenuation of oxidative stress mitigates the autistic-like behaviors in mouse model of maternal separation stress - Karimi, Parnian; Ghahfarroki, Mehryar Shahgholian; Lorigooini, Zahra; Shahrani, Mehrdad; Amini-Khoei, Hossein (Frontiers in Pharmacology, 2024)
Autism spectrum disorder (ASD) is a complex neurodevelopmental condition. Maternal separation (MS) stress is an early-life stress factor associated with behaviors resembling Autism. Both MECP2 and oxidative stress are implicated in the pathophysiology of Autism. Umbelliprenin (UMB) is a coumarin compound with various pharmacological properties. Our study aimed to investigate the potential effects of UMB in mitigating autistic-like behaviors in a mouse model subjected to MS stress, focusing on probable alterations in MECP2 gene expression in the hippocampus. MS paradigm was performed, and mice were treated with saline or UMB. Behavioral tests consisting of the three-chamber test (evaluating social interaction), shuttle box (assessing passive avoidance memory), elevated plus-maze (measuring anxiety-like behaviors), and marble-burying test (evaluating repetitive behaviors) were conducted. Gene expression of MECP2 and measurements of total antioxidant capacity (TAC), nitrite level, and malondialdehyde (MDA) level were assessed in the hippocampus. The findings demonstrated that MS-induced behaviors resembling Autism, accompanied by decreased MECP2 gene expression, elevated nitrite, MDA levels, and reduced TAC in the hippocampus. UMB mitigated these autistic-like behaviors induced by MS and attenuated the adverse effects of MS on oxidative stress and MECP2 gene expression in the hippocampus. In conclusion, UMB likely attenuated autistic-like behaviors caused by MS stress, probably, through the reduction of oxidative stress and an increase in MECP2 gene expression.